German Screen for Child Anxiety Related Emotional Disorders (SCARED): Reliability, Validity, and Cross-Informant Agreement in a Clinical Sample - Wiegand-Grefe Silke; Rosenthal Sandra; Romer Georg; Weitkamp Katharina; Daniels Judith (BMC, 2010)
Abstract Background The psychometric properties and cross-informant agreement of a German translation of the Screen for Child Anxiety Related Emotional Disorders (SCARED) were assessed in a clinical sample Methods 102 children and adolescents in outpatient psychotherapy and their parents filled out the SCARED and Youth Self Report/Child Behaviour Checklist (YSR/CBCL). Results The German SCARED showed good internal consistency for both parent and self-report version, and proved to be convergently and discriminantly valid when compared with YSR/CBCL scales. Cross-informant agreement was moderate with children reporting both a larger number as well as higher severity of anxiety symptoms than their parents. Conclusion In conclusion, the German SCARED is a valid and reliable anxiety scale and may be used in a clinical setting